Vibrational communication of Isoperla Banks from California and Oregon (Plecoptera: Perlodidae) - Sandberg, John B. (Illiesia, 2011)
The drumming signals of fourteen species of the stonefly genus Isoperla Banks from California and Oregon are reported. Monophasic, varied beat-interval and diphasic signal types were determined by graphing the mean interval pattern. Monophasic signals had a maximum mean interval difference of 10 milliseconds and varied beat-interval signals had greater than 10 millisecond interval differences. The diphasic signal was a continuous signal composed of monophasic, decreasing varied beat-interval and monophasic intervals. Signals are described for the first time for six species: I. baumanni Szczytko & Stewart, I. denningi Jewett, I. laucki Baumann & Lee, I. marmorata Needham & Claassen, I. pinta Frison and I. sordida Banks. Descriptions of new signal characters and signals from additional locations are provided for eight species: I. acula Jewett, I. adunca Jewett, I. bifurcata Szczytko & Stewart, I. miwok Bottorff & Szczytko, I. mormona Banks, I. quinquepunctata (Banks), I.roguensis Szczytko & Stewart and I. sobria (Hagen).
Keywords: entomologija; entomology; Plecoptera; vrbnice; Perlodidae; drumming signals; mate-finding behavior; stoneflies; California; Oregon